Determining of Physiological Maturity and Wax Coating for Inhibiting Snake Fruit var Gading Deterioration during Storage in Room Temperature - Santosa, Budi; Hulopi, Fauzia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
Snack fruit var. gading is a perishable horticultural product and non climacteric fruit that has room temperature shelf life about 6-7 days. This fruit should be ripe before harvesting and during storage does not undergo further ripening process. It has high respiratory rate that caused fast senescence. This research was aimed to determine harvesting time to obtain good quality and long shelf life of snake fruit. Also, it was objected to elucidate the effect of wax coating on quality changes during storage. The harvesting time of snake fruit was 5, 6, and 7 month after pollination. Wax coating (10%) was used to protect the fruits during storage. Glucose, fructose, sucrose, and tannin was determined after harvesting. The quality of snack fruits was assesed by panelists independently. The results showed that the best harvesting time of snack fruit was 6 months after pollination. Wax coating influenced the fruit quality and also could inhibit declining of sugar and tannin content of fruit. Wax coating could improve the quality of fruits during storage up to 2 weeks.Keywords: harvesting time, wax coating, snack fruit var. gading